Single Mothers in Malaysia: Survivability, Entrepreneurship and Empowerment - Suhaimi Mohd, Muhammad; Azwan Mohd Kamal, Mohd Khirul; Safwan Mohd Yusof, Muhammad; Ain Yusof, Nur (JASSP, 2021)
The incidence of single-parent families has been rising continuously where the divorce has become a popular solution for people in seeking the final clarity towards the marriage problems. This figure is consistent with the current trend worldwide upon this topic of single mothers. An enormous increase in the number of single mothers due to divorce has become a reasonable approach for the people in seeking the final clarity towards the marriage problems. In Malaysia, single mothers can be classified as in two variables which are parental death and spousal separation or divorce; parenting is a tough job without a spouse helping in a child's development. The incidence of single-parent families has been rising continuously where the divorce has become a popular solution for people in seeking the final clarity towards the marriage problems. This figure is consistent with the current trend worldwide upon this topic of single mothers. An enormous increase in the number of single mothers due to divorce has become a reasonable approach for the people in seeking the final clarity towards the marriage problems. In Malaysia, single mothers can be classified as in two variables which are parental death and spousal separation or divorce; parenting is a tough job without a spouse helping in a child's development. The aim of this study are to identify challenges face by single mother in Malaysia, policies on entrepreneurship, entrepreneurship activities and in Malaysia and survivability. This study apply qualitative method in describing challenges amongst single mother and policies on entrepreneurship by using data obtained from Department of Women Development in 2017 and previous studies. The results of the study show by developing policies and programs for single mothers, it could help them to survive for long period of time. This study contributes to the development of action plan in aiding single mothers in Malaysia to work and support single mothers from poverty.